Effects of a novel HSP90 inhibitor on estrogen receptor α signaling pathways in breast cancer cells - A. M. Scherbakov; D. V. Sorokin; D. I. Salnikova; M. V. Gudkova; O. E. Andreeva; A. L. Mikhaylova; N. A. Varabyeva; Yu. A. Piven (Успехи молекулярной онкологии, 2024)
Introduction. Heat shock proteins (HSP), also known as molecular chaperones, are a large family of proteins that play crucial roles in histogenesis, homeostasis, and the folding and functional regulation of numerous client proteins. Among them, HSP90 is a key player, particularly in supporting the growth of tumor cells. HSP90 impacts multiple carcinogenic signaling pathways, including BCR-ABL, Raf-1, AKT, human epidermal growth factor receptor 2 (ERBB2/HER2), hypoxia-inducible factor 1-α (HIF-1α), janus kinase 2 (JAK2), STAT3, p53, and estrogen receptor α (ERα). As a result, the search for new, selective inhibitors of this chaperone is a high priority in medicinal chemistry and oncology.Aim. To evaluate the antiproliferative activity of a novel HSP90 inhibitor, THB5T-1, on ERα-positive breast cancer cell lines and assess its anti-estrogenic potential and selectivity. Materials and methods. The study was conducted on hormone-dependent breast cancer cell lines MCF7 and T47D, along with the normal fibroblast line hFB-hTERT. The antiproliferative activity of THB5T-1 was measured using the MTT assay, while immunoblotting was employed to analyze the effects of HSP90 inhibition on cell signaling pathways. Anti-estrogenic activity was assessed in MCF7 cells via a reporter assay, and molecular modeling was used to construct a model of THB5T-1 interaction with the ligand-binding domain of ERα.Results. The half-maximal inhibitory concentration (IC50) of THB5T-1 was determined to be 4.3 μM for MCF7 cells and 5.6 μM for T47D cells. At a concentration of 25 μM, cell survival decreased to 20%. The selectivity index for THB5T-1 varied from 3.7 to 5.0 in different breast cancer cell lines. The compound’s effects on hormonal pathways in MCF7 cells, as observed via reporter assay and immunoblotting, were dose-dependent. These findings were further supported by molecular docking studies, showing THB5T-1 interaction with the ligand-binding domain of ERα. Additionally, the antiproliferative activity of THB5T-1 in MCF7 cells was associated with reduced expression of cell cycle regulators cyclin D1 and cyclin-dependent kinase 4 (CDK4). Significant efficacy of compound THB5T-1 in combination with a selective AKT inhibitor was revealed.Conclusion. Compound THB5T-1 demonstrated significant antiproliferative effects on ERα-positive breast cancer cells and exhibited high selectivity. Its anti-estrogenic effects highlight its potential as a selective inhibitor of the HSP90/ ERα/GREB1 pathway, effectively blocking ERα-mediated cell proliferation.